Programa de desenvolvimento de fornecedores e indução de comportamentos de melhoria contínua: estudo de caso da Natura Cosméticos - Sediyama, Roberto Seiti (2012)
As the competition between companies expands to the level of supply chain, it is necessary to improve supplier performance through efforts of the purchasing companies. Defined as 'focal company's effort to improve supplier performance and/or skills tailored to meet the needs of short and/or long-term purchasing company' (KRAUSE, 1999), the development of suppliers becomes a differential element in the search for superior performances of the actors in the supply chain. It is in this context that the work seeks a better understanding of the supplier’s development program of the company Natura Cosmetics, the QLICAR program, recognized as a distinctive program in the Brazilian market (REVISTA EXAME, 2011). The objective is to understand the practices of the supplier development program that sought to induce behaviors of continuous improvement in Natura’s suppliers. The methodological procedure was performed through a qualitative case study. The research instruments in this study were interviews and secondary data coming from three suppliers of the development program and the focal company. We identified three practices in QLICAR that seek to induce the behavior of continuous improvement in suppliers. They were evaluations, awards and meetings. Holistically, QLICAR practices complement the existing practices on suppliers. The evaluations proved as a complement of the indicators used in the suppliers and the meetings as an activity of strategic alignment between firms. The award was not unanimous as an incentive for the search for improvements. In the case examined, it was presented evidences that the practices of the supplier development program are seen differently among the actors involved.